Spectrum of Respiratory Distress in Newborn: A Study From a Tertiary Care Military Hospital - Raha, Biplob Kumar; Alam, Md Julfikkar; Bhuiyan, Mohammad Abdul Quddus (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Respiratory distress (RD) is a common problem in neonatal period. It is an important cause of neonatal mortality. There are many causes of respiratory distress, among them, transient tachypnea of newborn (TTN), respiratory distress syndrome (RDS) and perinatal asphyxia are commonest causes. Timely and appropriate therapy is essential to prevent ongoing injury and improve outcome. The aim of this study was to determine the prevalence and to identify the causes of respiratory distress in neonatal intensive care unit (NICU) in Combined Military hospital (CMH) Sylhet and to observe the hospital outcome of these babies. Material and Methods: A descriptive type of crosssectional study was conducted in CMH Sylhet over a period of one year from April 2018 to March 2019. All live newborns delivered at CMH Sylhet during the study period were included and observed for development of respiratory distress. Results: All newborns (n=287), delivered at this hospital over the period of 12 months, were observed for respiratory distress. The overall prevalence of respiratory distress was 19.2 %. Prevalence was 10.8 % in full term, 7.3 % in preterm and 1.1% in post term. There was male predominance (54.5%) and two third (71.1%) were born by cesarean section. Transient tachypnea of newborn was found to be the commonest 47.3% cause of respiratory distress followed by respiratory distress syndrome 29.1%, perinatal asphyxia (10.9%), congenital pneumonia 3.6%, congenital heart disease 3.6%, septicaemia 3.6% and meconium aspiration syndrome (MAS) 1.9%. All babies required high flow oxygen initially, subsequently Bubble CPAP and mechanical ventilation was required in 8 (14.5%) and 1(1.8%) cases respectively. Mortality was 1.8% in neonates with respiratory distress syndrome with pneumothorax with septicaemia requiring mechanical ventilation. Conclusion: In this series, RDS in newborn majority of cases were due to TTN followed by respiratory distress syndrome and perinatal asphyxia. Mortality was mainly related to pneumothorax with septicaemia, RDS was more common in births related to caesarian section. J Bangladesh Coll Phys Surg 2021; 39(1): 4-8